2021
DOI: 10.1111/prd.12369
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining homeostatic control of periodontal epithelial tissue

Abstract: Years of coevolution with resident microbes has made them an essential component of health. Yet, little is known about oral commensal bacteria’s contribution to and role in the maintenance of oral health and homeostasis. Commensal bacteria are speculated to play a host protective role in the maintenance of health. In this review, we describe and provide examples of the coordinate regulation that occurs between oral commensal bacteria and the host innate immune response to modulate and maintain oral homeostasis. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 101 publications
0
12
0
1
Order By: Relevance
“…For example, a study using the CRISPR/Cas9 system to engineer and test previously identified human haplotypes within the interleukin-8 gene (IL-8; also known as CXCL8) have provided new evidence of the active involvement of host genetics to increase neutrophil migration in vitro and hence its potential to influence an individual's susceptibility to disease [ 7 ]. Furthermore, there is growing awareness behind the host protective role of the microbial dental plaque biofilm as a key player for the maintenance of healthy homeostasis [ 8 , 9 ]. Studies by To et al and Myers et al have shown the unique immunosuppressive potential of healthy subgingival and supra-gingival plaque, respectively [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study using the CRISPR/Cas9 system to engineer and test previously identified human haplotypes within the interleukin-8 gene (IL-8; also known as CXCL8) have provided new evidence of the active involvement of host genetics to increase neutrophil migration in vitro and hence its potential to influence an individual's susceptibility to disease [ 7 ]. Furthermore, there is growing awareness behind the host protective role of the microbial dental plaque biofilm as a key player for the maintenance of healthy homeostasis [ 8 , 9 ]. Studies by To et al and Myers et al have shown the unique immunosuppressive potential of healthy subgingival and supra-gingival plaque, respectively [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a mutually beneficial relationship between the microbial community and the host ( Ye et al., 2013 ; Chang et al., 2021 ). For example, resident oral bacteria are able to prevent colonization by exogenous organisms, which have the potential to be pathogenic ( Shu et al., 2020 ).…”
Section: Oral Mucositismentioning
confidence: 99%
“…Oral epithelial cells are sentinel cells provided with a multitude of PRRs and upon PAMP stimulation produce interleukins (ILs), in particular IL-8 ( 149 ). IL-8 is mostly recognised via the neutrophil chemokine receptor CXCR2, which play a crucial role for the neutrophil recruitment into periodontal crevice ( 150 ).…”
Section: Dysregulated Immunitymentioning
confidence: 99%